1999
DOI: 10.1021/jp982735k
|View full text |Cite
|
Sign up to set email alerts
|

Spin−Orbit Effects, VSEPR Theory, and the Electronic Structures of Heavy and Superheavy Group IVA Hydrides and Group VIIIA Tetrafluorides. A Partial Role Reversal for Elements 114 and 118

Abstract: Relativistic effective core potentials and spin-orbit operators are used in relativistic configuration interaction calculations to explore the effects of spin-orbit coupling on the electronic structures of atoms and molecules of elements 114 and 118. The monohydrides of group IVA and the tetrafluorides of group VIIIA are examined in order to provide examples of trends within families among the various periods. The spin-orbit effect is found to play a dominant role in the determination of atomic and molecular p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 33 publications
6
27
2
Order By: Relevance
“…In the light of the atomic results above, this is not surprising: the bond length is too short for the 8s to have a significant bonding effect, and the cost of promotion is too high. This is at variance with the findings of Nash and Bursten for 117H [12], whose work is based on spin-orbit CI based on spinfree calculations with an AREP. It is possible that the analysis in terms of spin-free eigenfunctions or the AREP itself places too much emphasis on the 8s.…”
Section: Hydridescontrasting
confidence: 82%
See 2 more Smart Citations
“…In the light of the atomic results above, this is not surprising: the bond length is too short for the 8s to have a significant bonding effect, and the cost of promotion is too high. This is at variance with the findings of Nash and Bursten for 117H [12], whose work is based on spin-orbit CI based on spinfree calculations with an AREP. It is possible that the analysis in terms of spin-free eigenfunctions or the AREP itself places too much emphasis on the 8s.…”
Section: Hydridescontrasting
confidence: 82%
“…This indicates that bonding involves both the valence and subvalence spinors, much more so than for 114H. The result for 114H is somewhat at variance with previous work, for which a minimum around 195-200 pm with a dissociation energy from 0.2-0.5 eV is found [6,12,16,18], based on DFT or CCSD(T) calculations. The CCSD(T) calculations are on the lower end of this range, whereas DFT gives larger values and is likely to overestimate the binding.…”
Section: Hydridessupporting
confidence: 57%
See 1 more Smart Citation
“…Influence of the SO interaction on the geometry of 118F 4 was investigated by RECP-SOCI and -CCSD calculations [147,159,160]. It was shown that a D 4h geometrical configuration known for XeF 4 and RnF 4 becomes about 0.2 eV less stable than the T d one.…”
Section: P Elementsmentioning
confidence: 99%
“…Experimental excited levels in free Pb atoms could be reproduced in calculations to 0.06 eV [16]. Comparison of some ionization potential values [16][17][18], is shown in Table 2. The potentials for SHE seem trustworthy because of good agreement with experimental data for the known homologues.…”
Section: Chemistry Of She -Theorymentioning
confidence: 98%